Haemato-Biochemical Changes in Canine Demodicosis Treated with Allopathic and Herbal Preparations - Gupta, Naman; Bagherwal, Rajendra K.; Mehta, Hemant K.; Agrawal, Vivek; Aich, Ranjit (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
A study was conducted on 18 dogs suffering from demodectic mange brought to the Veterinary Clinical Complex (VCC) of the Collegein Mhow and at Private Clinics, Indore. The dogs were randomly subdivided into three groups having 6 dogs in each group. Group I dogs were treated with Inj. Ivermectin 1% S/C + solution Amitraz 12.5% @ 5 mL/L applied topically once a week for 6 weeks. Group II dogs were treated with spot-on preparation of Moxidectin 2.5% + Imidacloprid 10% applied topically once a week for 6 weeks, while Group III dogs were treated with topical application of herbal preparation containing extract of Azadirachta indica (Neem) leaves + Aloe vera gel daily twice for six weeks. The treatment response of animals was evaluated by improvement in clinical signs and haemato-biochemical parameters. No side effects were reported in any group. The results showed significant improvement in haemato-biochemical parameters. Combination of Inj. Ivermectin 1% S/C + solution Amitraz 12.5% was found to be superior to the herbal and spot-on preparations.
Keywords: Allopathic drugs; Amitraz; Canines; Demodicosis; Herbal drugs; Imidacloprid; Ivermectin